2022
DOI: 10.3389/fcell.2022.943067
|View full text |Cite
|
Sign up to set email alerts
|

Childhood social isolation causes anxiety-like behaviors via the damage of blood-brain barrier in amygdala in female mice

Abstract: Social interaction plays an essential role in species survival for socialized animals. Previous studies have shown that a lack of social interaction such as social isolation, especially in the early-life phase, increases the risk of developing mental diseases in adulthood. Chronic social stress alters blood-brain barrier (BBB) integrity and increases peripheral cytokines to infiltrate the brain, which is linked to the development of depressive-like behaviors in mice, suggesting that BBB function is crucial in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 83 publications
0
9
1
Order By: Relevance
“… 64 On the contrary, 6 weeks of SI in young male rats 24 and mice 20 as well as 4 weeks of SI in adult mice 65 and prairie voles 66 induced depression-like behavior. However, these results were not replicated either in our study or the study by Wu et al 63 Differences in species, strain, age, cage enrichment, housing conditions, and duration of SI may account for the lack of substantial depression-like behavior in socially isolated animals in this study.…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“… 64 On the contrary, 6 weeks of SI in young male rats 24 and mice 20 as well as 4 weeks of SI in adult mice 65 and prairie voles 66 induced depression-like behavior. However, these results were not replicated either in our study or the study by Wu et al 63 Differences in species, strain, age, cage enrichment, housing conditions, and duration of SI may account for the lack of substantial depression-like behavior in socially isolated animals in this study.…”
Section: Discussioncontrasting
confidence: 99%
“…Our results corroborate to some extent with those of a recent study that used the same strain and age of animals of both sexes and chronic SI as in our study and found no depression-like behavior in either males or females. 63 However, the FST by Wu et al, was conducted during the dark cycle, included the adaptation stage (pre-test one day before the actual test), and all mice were able to smell one another. Based on additional evidence from this study, neither male nor female mice developed depression-like symptoms after 8 weeks of SI.…”
Section: Discussionmentioning
confidence: 99%
“…The most established indicators of emotional behavior in the open field test are ambulation [ 37 , 38 ]. It has been proposed that the fear or anxiety response of the animal exposed to a new environment is accompanied by low ambulation, especially in the central zone [ 37 , 38 , 39 , 40 , 41 ]. This study showed a decreased effect on both the central square entry and duration, which may happen due to the consumption of calabash chalk [ 3 , 37 ].…”
Section: Discussionmentioning
confidence: 99%
“…A down-regulation of TJ protein Claudin-5 has been observed in the nucleus accumbens (NAc) and in the medial prefrontal cortex (mPFC) of mice exposed to social defeat stress (2,32). Furthermore, the work of Wu and colleagues (2022) demonstrated a link between Claudin-5 down-regulation and the emergence of anxious-like behaviour in female mice, as well as a decrease of these behaviours in mice under social isolation by overexpressing Claudin-5 in the amygdala (33). Similarly, in the chronic social defeat murine model of depression, the expression of endothelial Claudin-5 is reduced along with abnormal blood vessel morphology in the NAc of stress-susceptible but not resilient mice (32).…”
Section: Discussionmentioning
confidence: 99%